2017
DOI: 10.1155/2017/2625030
|View full text |Cite
|
Sign up to set email alerts
|

Goldenhar Syndrome with Dextrocardia and Right Pulmonary Hypoplasia: An Unusual Association

Abstract: Goldenhar syndrome (GS), a rare condition, occurring due to defect in development of first and second branchial arches, is characterized by a combination of various anomalies involving face, eyes, ears, vertebrae, heart, and lungs. The etiology of GS is not fully known, although various hypotheses have been proposed along with its genetic association and many other causes. Facial asymmetry and hypoplasia of the mandible are characteristic features of GS along with microtia and preauricular appendages and pits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…A comprehensive search of PubMed and Embase was performed to identify studies using MeSH terms and keywords “HFM” or “oculo-auriculo-vertebral syndrome” or “Goldenhar Syndrome” or “microtia”. Only thred cases[ 14 - 16 ] of HFM combined with pulmonary hypoplasia and dextrocardia were retrieved and reviewed (Table 1 ). Two patients were male with an ipsilateral malformation (right-side involvement), and one case was female with left HFM.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive search of PubMed and Embase was performed to identify studies using MeSH terms and keywords “HFM” or “oculo-auriculo-vertebral syndrome” or “Goldenhar Syndrome” or “microtia”. Only thred cases[ 14 - 16 ] of HFM combined with pulmonary hypoplasia and dextrocardia were retrieved and reviewed (Table 1 ). Two patients were male with an ipsilateral malformation (right-side involvement), and one case was female with left HFM.…”
Section: Discussionmentioning
confidence: 99%
“…El diagnóstico está basado en los hallazgos unilaterales más comunes: defectos auriculares (incluyendo hipoplasia ótica y trago accesorio, 94 %), anomalías faciales (microsomía hemifacial y micrognatia, 76 %), anomalías oculares (dermoides epibulbares y/o coloboma, 65 %) y anomalías vertebrales (hemivértebras). La mayoría de los rasgos fenotípicos son ipsilaterales al lado afectado de la cara (3,9). La ecografía tridimensional es útil en la evaluación de la cara fetal (10).…”
Section: Caso Clínicounclassified
“…El pronóstico depende de la gravedad y combinación de malformaciones/ defectos sistémicos asociados. Las formas graves pueden causar discapacidad importante (2,3). Se presenta un caso de diagnóstico prenatal de síndrome de Goldenhar.…”
Section: Introductionunclassified
“…Some studies have reported familial transmission [ 15 ] suggesting this leads to autosomal recessive inheritance (two copies of an abnormal gene being present) or dominant inheritance (an overly dominant gene causing a mutation). Multifactorial inheritance (genetic and environmental factors) has also been proposed [ 16 ]. Terhaar's 1972 [ 17 ], discovery of monozygotic twins concordant for OAVs pointed towards a genetic explanation for this syndrome.…”
Section: Introductionmentioning
confidence: 99%